The link between infant neuropsychological risk and childhood antisocial behavior among males: The moderating role of neonatal health risk. (December 2016) - Jackson, Dylan B.; Newsome, Jamie
Abstract: Purpose: The current study examines the association between infant neuropsychological risk and childhood antisocial behavior, and whether neonatal health risk moderates this association. Methods: Longitudinal data from the Early Childhood Longitudinal Study: Birth Cohort (ECLS-B) were analyzed using hierarchical regression. Results: The findings suggest that the association between infant neuropsychological risk and childhood antisocial behavior is contingent on both biological sex and neonatal health risk. Males who experienced neonatal health risks exhibited significantly higher levels of childhood antisocial behavior as neuropsychological risk during infancy increased. Conclusions: The relationship between neuropsychological risks and childhood antisocial behavior may be exacerbated by neonatal health risks among males. Implications for theory, prevention, and intervention are considered. Highlights: Infant neuropsychological risk predicts childhood antisocial behavior among males. Neonatal health risk significantly moderates this association. Neuropsychological risk only predicts antisocial behavior when health risks are present. Early risk assessment should account for both neuropsychological and health risks.